PsycEXTRA Dataset 2000
DOI: 10.1037/e318522004-001
|View full text |Cite
|
Sign up to set email alerts
|

Kidnaping of Juveniles: Patterns From NIBRS

Abstract: The kidnaping of a child is a crime that tears at the fabric of society. Until recently, the nature and scope of the problem have been unclear because existing crime data collection systemssuch as the FBI's Uniform Crime Reporting (UCR) system and OJJDP's National Incidence Studies of Missing, Abducted, Runaway, and Thrownaway Children-do not collect law enforcement data on kidnaping. Fortunately, that is about to change. In partnership with the Bureau of Justice Statistics, the FBI is supplanting the UCR with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 6 publications
0
35
0
Order By: Relevance
“…Legal definitions of kidnapping, however, are not limited to crimes perpetrated by strangers against children and do not require that the victim be transported or even detained for a lengthy period of time. 1 Indeed, descriptive studies on juvenile kidnappings confirm that many incidents differ considerably from the sensationalized cases represented in the media and frequently involve family member and acquaintance perpetrators (Finkelhor, Hammer, & Sedlak, 2002;Finkelhor & Ormrod, 2000;Finkelhor & Shattuck, 2012;Finkelhor et al, 1992).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Legal definitions of kidnapping, however, are not limited to crimes perpetrated by strangers against children and do not require that the victim be transported or even detained for a lengthy period of time. 1 Indeed, descriptive studies on juvenile kidnappings confirm that many incidents differ considerably from the sensationalized cases represented in the media and frequently involve family member and acquaintance perpetrators (Finkelhor, Hammer, & Sedlak, 2002;Finkelhor & Ormrod, 2000;Finkelhor & Shattuck, 2012;Finkelhor et al, 1992).…”
Section: Introductionmentioning
confidence: 97%
“…Limited research coupled with intense media coverage of select and often atypical incidents contributes to misconceptions about the nature of kidnapping in the United States (Boudreaux, Lord, & Etter, 2000;Finkelhor, Hotaling, & Sedlak, 1992;Finkelhor & Ormrod, 2000;Miller, Kurlycheck, Hansen, & Wilson, 2008). In the stereotypical case, kidnapping is perpetrated by a stranger who transports a victim -usually a child -to a different location for a considerable length of time (Finkelhor et al, 1992).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…This finding is far from certain, though. Girls, for example, have been found to have a higher likelihood of experiencing several forms of missing event, notably running away (Sanchez et al 2006), and non-family abductions (which, as argued above, might well be the most dangerous of the missing events) (Finkelhor and Ormrod 2000). Other research, however, has found that the proportion of runaways who are male and female is more or less equal .…”
Section: Review Of Literaturementioning
confidence: 93%